2023
DOI: 10.1097/md.0000000000033837
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between stress and sleep quality: The mediating effect of fatigue and dizziness among patients with cardiovascular disease

Abstract: Cardiovascular disease is the leading cause of non-noncommunicable disease mortality worldwide. Therefore, this study analyzes the mediating effect of dizziness and fatigue in the relationship between stress and sleep quality in patients with heart disease. This study was conducted on patients with heart disease diagnosed by a cardiologist from December 7, 2021 to August 30, 2022 at the Outpatient Department of Cardiology at Hanyang University Hospital in Guri-si, Gyeonggi-do. To verify the serial multiple med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The relationship between fatigue and sleep should not be ignored. The latest study reported that both physical and psychological fatigue is associated with sleep quality ( 32 ). A systematic review concluded that there is a significant correlation between short sleep duration, fatigue, and increased incidence of CHD ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between fatigue and sleep should not be ignored. The latest study reported that both physical and psychological fatigue is associated with sleep quality ( 32 ). A systematic review concluded that there is a significant correlation between short sleep duration, fatigue, and increased incidence of CHD ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…[17,18] Disturbed sleep and poor sleep quality are essential predictors of fatigue. [19][20][21] In terms of the factors associated with fatigue, mechanisms such as overexertion, sleep disturbances, stress, depression, shoulder pain or disability, infections, endocrine disorders, and metabolic conditions have been suggested. [15,16,20,21] However, none of these factors alone can fully explain fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In terms of the factors associated with fatigue, mechanisms such as overexertion, sleep disturbances, stress, depression, shoulder pain or disability, infections, endocrine disorders, and metabolic conditions have been suggested. [15,16,20,21] However, none of these factors alone can fully explain fatigue. Therefore, it is necessary to analyze the various factors influencing fatigue, considering their impact on physical fatigue and mental fatigue.…”
Section: Introductionmentioning
confidence: 99%